Molecular analysis of ancestry informative markers (AIMs-INDELs) in a high altitude Ecuadorian mestizo population affected with breast cancer. (December 2017) - López-Cortés, A.; Echeverría-Garcés, G.; Burgos, G.; Zambrano, A.K.; Cabrera-Andrade, A.; García-Cárdenas, J.M.; Salazar, C.; Leone, P.E.; Paz-y-Miño, C.
Abstract: Breast cancer (BC) is the leading cause of cancer-related death among women. BC is a heterogeneous disease differing in genomic complexity, key genetic alterations, and clinical prognosis. Given the description of the Ecuadorian population as multiethnic, made up of African, Native American, and European groups, this research is an initial evaluation of the potential benefits that would be obtained by generating a haplotype map of the Ecuadorian population to improve precision medicine. The aim was to estimate the original proportion of each inferred population and to determine the underlying population in women affected with BC. The ancestral proportion among Africans, Europeans, and Native Americans in Ecuadorian women was calculated through 45 ancestry informative markers (AIMs) and the comparison to the Human Genome Diversity Project panel. The resulting allele frequencies in affected women indicated prevalence of the Native American ancestral component with 60.58%, and minor proportion for the European and African components with 34.57% and 3.7%, respectively. These results suggest that the genetic variations expressing BC in Ecuadorian women could have been caused by the insertion of certain genetic characteristics of the Native American groups as consequence of ancestral migration towards South America.